A Standardized Method for Measuring Anti-F VIII:C Inhibitors in Haemophilia A by Coagulation Inhibition in Agarose Gel - Jorquera, J I; Carmona, E; Aznar, J A; Peiró, A; Sánchez-Cuenca, J M (Thrombosis and Haemostasis, 1985)
Antibodies against factor-VIII coagulant activity can appear in haemophilic patients and, although infrequently, can affect individuals not suffering from Haemophilia A. The Oxford and Bethesda methods are presently the most commonly used techniques for measuring these antibodies. Both methods are time-consuming and not suitable for the screening of large risk groups.An appropriate method for screening these coagulation inhibitors is that described by P. Bird in 1975. It is based on inhibition of the coagulation produced when plasma samples containing inhibitors diffuse in agarose gels mixed with normal platelet rich plasma (PRP). However, this technique is highly dependent on the variability derived from the use of PRP (amount of coagulant factor-VIII, number of platelets, etc.).In an attempt to avoid these disadvantages, Bird’s method has been modified by using standardized commercial reagents (lyophilized plasma with 100% factor-VIII coagulant activity, purified fibrinogen, and platelet Factor 3) instead of PRP. The sensitivity reaches 0.8 Bethesda units and the correlation with the Bethesda method is r = 0.964, p <0.001. This newly developed method is as simple as Bird’s, and appears to be at least, as accurate and reproducible as the Bethesda method.
Keywords: Factor-VIII inhibitors; Coagulation inhibition; Agarose gel